Questionable Practices? Relying on Individual Teacher Resilience in Remote Schools - Sullivan, Anna; Johnson, Bruce (Australian and International Journal of Rural Education, 2012)
Early career teachers eager to find employment are often encouraged by employers to accept positions in remote locations which are traditionally difficult to staff. This paper reports research that examined a case study of a graduate teacher employed in a remote school. Drawing on resilience theory, we challenge the profession to consider whether in fact employers are relying on the personal resilience of early career teachers to cope with the rigors of teaching in remote schools and are remiss for not providing adequate support at school and system levels.